Space - Young, Ruth M.; Kelly, Walter; Taggart, Mary Kaye. (Westminster, CA : Teacher Created Materials, 1996)
Contains sample lesson plans, literature reviews, and activities designed to help teachers plan a thematic unit about space.
"TCM 587"--Cover.
"Thematic unit.".
Includes bibliographical references (p. 77).
Professional
Keywords: Astronomy -- Study and teaching; Creative activities and seat work; Literature -- Study and teaching; Teaching -- Aids and devices; Astronomy -- Study and teaching; Creative activities; Literature -- Study and teaching; Teaching -- Aids and devices; Outer space -- Study and teaching; Outer space -- Study and teaching